Perineum: Erika Lopez - Debra A Castillo (Studies in 20th & 21st Century Literature, 2017)
Erika Lopez is the author of five lavishly illustrated, fictionalized memoirs as well as a postcard book and a performance piece, “Nothing Left but the Smell.” All of her books are road tales of sorts, texts that grapple with the inchoate and often illegible need to assert herself as bi: bi-racial, bi-sexual, bi-cultural, bi-coastal, but also more and different than merely bi (“I contain multitudes,” said Walt Whitman), disrespectful of boundaries, genders, and genres, and unwilling to settle down with one person or one story even when the constant movement and empting out exhausts her. Even worse, in some ways; her narrator is a curly haired, dark-skinned, large woman in a skinny world, an imposingly visible Latina who channels the dominant culture for her own purposes. “Perineum”—which she illustrates in text and image as a set-in-motion, in-between place—is one name for the challenge Erika Lopez presents us. She is too drawn to heterosex for the gay crowd, too elite-educated Quaker lady for pc scholars who share her educational credentials, not ghetto enough for the hood. The perineum is Lopez’s uncomfortable site of enunciation, set in motion and refusing to be pinned down in one place or as one identity.
Keywords: Erika Lopez; Latina writers; graphic novels; fictionalized memoir; queer writers; Lap Dancing for Mommy; Flaming Iguanas; Mad Dog; Hoochie Mama